Predicting lethal outcome risks in patients with craniomaxillofacial trauma and polytrauma by the ISS and NISS - Shumynskyi, I.; Sabadosh, M.; Gurianov, V.; Kopchak, A. (General Surgery, 2022)
Multiple papers reveal no reliable difference between early and delayed maxillofacial injuries treatment in postoperative complications in patients with craniomaxillofacial trauma and polytrauma. A choice factor of the treatment tactics is the lethal outcome risk, as well as the lethal outcome prognosis. In order to objectivize the severity of trauma authors suggested the assessment scores which represent patient’s condition severity in points and provide lethal outcome risk estimation, — Injury Severity Score (ISS) and New Injury Severity Score (NISS), each with advantages and disadvantages of prognosing the lethal outcome. Though, the data on its preciseness and informativeness regarding patients with combined craniomaxillofacial trauma are limited, and the results, obtained from various authors, seem to be controversial. Objective — to identify and compare the threshold (critical) values of the ISS and NISS assessment scales which predict the lethal outcome risks in patients with craniomaxillofacial trauma and polytrauma. Materials and methods. During 2016 — 2019 years 503 patients were treated due to maxillofacial traumas and associated injuries. Patients age ranged from 18 till 91 years, (average age — 30.5 years). There was a male predominance in the sample (84.3 %). Facial bone fractures occurred in 70 % of cases (352 patients). Mainly after assaults (44 %), falls (20 %) and motor‑vehicle accidents (16 %). The other etiological factors included occupational traumas (0.5 %), sport traumas (1 %) and unknown aetiology traumas. The study evaluated patients with facial and concomitant injuries, who received multidisciplinary treatment in a specialized trauma hospital. Values of Injury Severity Score and New Injury Severity Score were statistically analyzed to evaluate effectiveness in prognosing lethal outcome risks. Results. Mortality in the sample was 3 % (15 patients). With the optimum cut‑off value of ISS > 24, lethal outcome prognosis model sensitivity yields 93.3 %, specificity — 91.4 %. With the optimum cut‑off value NISS > 36, the lethal outcome prognosis sensitivity yields 86.7 %, its specificity 92.4 %. Conclusions. ISS and NISS demonstrate similar effectiveness in prognosing lethal outcome risks. The difference of area under the curve of both trauma severity estimation methods is not statistically significant (р = 0.651). Both indicators could be used in daily practice in specialized hospitals to assess the patient’s condition and determine priority of treatment steps.